Regionalism under the WTO, an impediment or a spur to trade and development in the multilateral trading system: a case study of the EAC - Namara, Justine (University of the Western Cape, 2013)
Magister Legum - LLM === This research paper pays particular attention to the EAC because of its unique composition of four LDCs46 and 1 DC47 and the fact that three of these countries are landlocked least developed countries (LLDCs).48 The EAC was notified as a RTA to the WTO under the Enabling Clause on 9 October 2000 and registered as a Custom Union49 under WT/COMTD/N/14.50 The notification of the EAC under the Enabling Clause is due to the nature of composition of members therein and to the fact that the Enabling Clause does not require regional trading arrangements to cover substantially all trade, or to achieve free trade in the bloc within ten years after notification. Additionally, it provides an avenue for giving special consideration to the LDCs through making concessions and contributions,51 allows automatic exemptions from MFN (non-discrimination) treatment in favour of DCs,52 and thus allows other WTO members to accord more favourable treatment to DCs in many cases without according the same treatment to other WTO members.53. === South Africa